Developing novel anthelmintics: the stability of cysteine proteinase activity in a supernatant extract of papaya latex. Issue 10 (October 2021) - Mansur, F.A.F.; Luoga, W.; Behnke, J.M.; Buttle, D.J.; Duce, I.R.; Garnett, M.C.
Abstract: Plant derived cysteine proteinases (CPs) have long been known to possess anthelmintic properties but have attracted renewed attention recently because of the acute need to discover novel methods for controlling helminth infections as a result of increasing drug resistance. However, surprisingly little is known about the stability of these proteins under typical storage and in vivo exposure conditions. We found that CPs in a supernatant preparation from papaya latex (PLS) were stable during the initial refinement process and when stored under low temperatures, but lost activity during dialysis and within 7 days of storage when kept at ambient temperature (18–20 °C). The enzyme activity in PLS was not affected by repeated freeze-thaw cycles and was also stable under typical in vitro assay conditions at 37 °C used for quantifying effects on helminths. Active enzyme activity was still detectable in the colon 3–4 h after oral administration in rodent models. Abstract : Papaya latex supernatant; Cysteine proteinase; Anthelmintic; Enzyme activity.